A first look at women's perspectives on noninvasive prenatal testing to detect sex chromosome aneuploidies and microdeletion syndromes. (6th April 2015) - Agatisa, Patricia K.; Mercer, Mary Beth; Leek, Angela C.; Smith, Marissa B.; Philipson, Elliot; Farrell, Ruth M.
Abstract Objective The aim of this study is to explore women's opinions about the use of noninvasive prenatal testing (NIPT) to assess the risk of sex chromosome aneuploidies and microdeletion syndromes. Methods Focus groups were conducted with women who were currently pregnant or had recently delivered. Qualitative analysis using interpretive description was used to generate study findings. Results Thirty‐one women (mean age 32.4 years) participated in the focus groups. Participants were unfamiliar with sex chromosome aneuploidies but expressed support for the use of NIPT to detect these conditions. Participants were uncertain about the utility and actionability of receiving information about microdeletion syndromes with variable or unknown phenotypic expression. Participants voiced their desire to be informed of all conditions assessed by NIPT prior to testing. They considered clinicians to be the key provider of such information, although stated that patients have a responsibility to be knowledgeable prior to testing in order to support informed decision making. Conclusions The use of NIPT to identify sex chromosome aneuploidies and microdeletion syndromes will introduce new challenges for clinicians to ensure pregnant women have the information and resources to make informed choices about NIPT when used for these conditions. © 2015 John Wiley & Sons, Ltd.